Sarcoplasmic/endoplasmic reticulum Ca(2+) ATPase C674 promotes ischemia- and hypoxia-induced angiogenesis via coordinated endothelial cell and macrophage function - Mei, Yu (J Mol Cell Cardiol, 2014)
Ischemia is a complex phenomenon modulated by the concerted action of several cell types. We have identified that sarcoplasmic/endoplasmic reticulum Ca(2+) ATPase 2 (SERCA 2) cysteine 674 (C674) S-glutathiolation is essential for ischemic angiogenesis, vascular endothelial growth factor (VEGF)-mediated endothelial cell (EC) migration and network formation. A heterozygote SERCA 2 C674S knockin (SKI) mouse shows impaired ischemic blood flow recovery after femoral artery ligation, and its EC show depleted endoplasmic reticulum (ER) Ca(2+) stores and impaired angiogenic behavior. Here we studied the role of SERCA 2 C674 in the interaction between ECs and macrophages in the context of ischemia and discovered the involvement of the ER stress response protein, ER oxidoreductin-1α (ERO1). In wild type (WT) mice, expression of ERO1 was increased in the ischemic hind limb in vivo, as well as in ECs and macrophages exposed to hypoxia in vitro. The increase in ERO1 to ischemia/hypoxia was less in SKI mice. In WT ECs, both vascular cell adhesion molecule 1 (VCAM1) expression and bone marrow-derived macrophage adhesion to ECs were increased by hypoxia, and both were attenuated in SKI ECs. In WT ECs, ERO1 siRNA blocked hypoxia-induced VCAM1 expression and macrophage adhesion. In WT macrophages, hypoxia also stimulated both ERO1 and VEGF expression, and both were less in SKI macrophages. Compared with conditioned media of hypoxic SKI macrophages, conditioned media from WT macrophages had a greater effect on EC angiogenic behavior, and was blocked by VEGF neutralizing antibody. Taken together, under hypoxic conditions, SERCA 2 C674 and ERO1 enable increased VCAM1 expression and macrophage adhesion to ECs, as well as macrophage VEGF production that, in turn, promote angiogenesis. This study highlights the hitherto unrecognized interaction of two ER proteins, SERCA 2 C674 and ERO1, which mediate the EC and macrophage angiogenic response to ischemia/hypoxia.